Exploring the Charge Dynamics and Energy Loss in Ternary Organic Solar Cells with a Fill Factor Exceeding 80%. Issue 31 (27th June 2021) - Zeng, Yihan; Li, Danqin; Xiao, Zuo; Wu, Hongbo; Chen, Zeng; Hao, Tianyu; Xiong, Shaobing; Ma, Zaifei; Zhu, Haiming; Ding, Liming; Bao, Qinye
Abstract: Ternary architecture is a promising strategy to enhance power conversion efficiencies (PCEs) of organic solar cells (OSCs). However, among all the photovoltaic parameters that govern the final PCEs, the fill factor (FF) for ternary OSCs is generally below 78%, limiting solar cells' performance. Here, charge dynamics in the ternary cells PM6:DRTB‐T‐C4:Y6 with a FF of 80.88% and a PCE of 17.05% are thoroughly investigated by a series of transient characterization technologies, including transient absorption spectroscopy, transient photovoltage, and transient photocurrent measurements. The impressive FF results from effective exciton dissociation, enhanced charge transport and suppressed recombination in ternary cells. Moreover, the correlation between the measured FF and the charge recombination‐extraction competition is quantitatively analyzed by using a circuit model. The ternary cells also show small energy loss ( E loss ). The findings here provide insight into achieving high‐FF and low‐ E loss ternary OSCs. Abstract : Charge dynamics and energy loss ( E loss ) in ternary organic solar cell (OSCs) with an impressive fill factor (FF) of 80.88% are thoroughly investigated by transient characterization techniques, which is expect to aid development of high‐FF and low‐ E loss ternary OSCs.